IMPACTS OF PRIVATE COLLEGES OF EDUCATION SELF-FINANCING ON LECTURERS’ JOB COMMITMENT. (Journal of Association of Educational Management and Policy Practitioners, 2024)
This paper examined the impacts of private Colleges of Education self- financing on lecturers‘  job commitment. The research design was the expost-facto design. The study was guided by three research questions. The population comprised all the academic staff in some selected private Colleges of Education in north central, Nigeria. The instrument used for data collection was a structured questionnaire titled ‗Questionnaire on the Impact of Private Colleges of Education Financing themselves on Lecturer Job Performance (QIPCEFLJP). The instrument was subjected to face and content validity by experts with a reliability coefficient of 0.78 obtained through Cronbach Alpha reliability estimates. The instrument was administered personally by the researcher while data collected was analyzed in relation to the research questions using mean and standard deviation. The benchmark for the acceptance value for each item was 2.5 and above. The study revealed that private Colleges of Education selffinancing affect lecturers job commitments as it affectstheir salary and job security. It was recommended that government should intervene to assist the private Colleges of Education in funding through donations and provision of facilities through TETFund.; better pay scale or standard with annual increments should be set for academic staff and policies against willful termination and disengagement should be put in place to discourage employers in private Colleges of Education from doing so at will. Keywords: Private Colleges of Education, self – financing, Job Commitment.